SPATIAL DISTRIBUTION OF TUNA LARVAE IN THE BANDA SEA WITH RELATION TO ITS CONSERVATION - Romdon, Ahmad; Fadli, Muhammad; Hehuwat, Yance; Pay, La; Satrioajie, Widhya Nugroho; Syahailatua, Augy (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2019)
Tuna is the single important export fishery commodity in Indonesia, which The Banda Sea is one of the important tuna fishing ground in which it belongs to fisheries management area (FMA) 714. More recently, some areas of the Banda Sea have been preserved for tuna conservation since January 2015 because it is indicated as the spawning area. Despite the conservation area has been enacted, information on the distribution of tuna larvae as a key variable for establishing conservation area in the Banda Sea is very limited. This study aims to provide the information on the tuna larvae encompassing the spatial distribution and tuna larval development stage as an important input to establish tuna conservation area. Tuna larvae data were collected from several surveys that were done in the Banda Sea over 4 decades. Those study consisted of 21 surveys by using three types of gears to collect tuna larvae sample. Total of 143 stations have been sampled from these surveys and tuna larvae were found in 57 stations. The body length of larvae tuna was 7.36 ± 0.33 mm (mean ± SE). Overall, tuna larvae found in the Banda Sea were in the pre-flexion, flexion, and post-flexion stage. Meanwhile, tuna larvae in pre-flexion stage found in the nearshore area. We concluded this study result supported the hypothesis that tuna may spawn in the Banda Sea. Therefore, more studies on tuna larvae need to be conducted to clarify properly the Banda Sea is an important tuna conservation location.